Exploring the roles of school governing bodies in the management of school finances in Limpopo Province - Mmako, Emanuel Tebogo (University of the Free State, 2024)
The study explored the role of school governing bodies (SGBs) in managing school finances in Limpopo, focusing on concerns that cases of SGB dysfunctionality continue to be referred to the Department of Basic Education (DBE) and Provincial Education Departments (PED). This suggests a longstanding failure to achieve value for money in schools. The research was framed using the principal-agent (P-A) theory and adopted a constructivist ontological worldview. An interpretive paradigm was used to construct the social reality of the research problem. Data was collected from SGBs of five public ordinary schools in the Capricorn South District, Limpopo. The selection included three no-fee schools and two fee-paying schools to provide a broad perspective. A case study approach was adopted, and thematic analysis was applied to data from financial document reviews, observations, interviews, and focus groups. The study identified several factors influencing school fiscal management, including both internal and external stakeholders. Findings revealed gaps in knowledge of applicable legislation, especially in no-fee schools, the appointment of ineligible independent reviewers for financial statements, unethical practices by senior state officials, and issues with external auditors. These challenges contribute to inefficiencies in SGB fiscal management. In response to these findings, the study recommends several interventions: the creation of a resolute SGB capacity-building directorate, implementation of robust training programs, a review of the eligibility criteria for independent financial reviewers, and enforcement of accountability measures for officials engaging in unethical conduct. These recommendations aim to enhance SGB effectiveness in managing school finances, ensuring better outcomes for schools, especially in poorer communities.
Thesis (Ph.D. (Education Management and Leadership))--University of the Free State, 2024
Keywords: School governing bodies; School finances; Financial management; Limpopo Province; Education management